Molecular Frontiers in Biodiversity Research From Bangladesh: A Review (Bioresearch Communications, 2026)
Bangladesh harbors a rich and unique biodiversity and is home to numerous threatened species of different categories that are vital for its ecological balance and sustainable development. In recent years, molecular approaches have emerged as powerful tools for studying and conserving this biodiversity and threatened organisms, enabling precise species identification, uncovering cryptic diversity, helping to make informed management strategies. This review aims to synthesize recent advances in molecular taxonomic research on Bangladesh’s flora and fauna, with a particular emphasis on the applications of DNA barcoding across marine, freshwater, and terrestrial taxa. The review highlights that, despite the remarkable biodiversity in Bangladesh, only a fraction of these species has been genetically characterized. DNA barcoding initiatives have progressed notably in fishes, arthropods, and fungi, but remain limited for plants and several vertebrate and invertebrate groups, particularly in avian species. This disparity underscores a significant gap between the country’s known biodiversity and its molecular-level validation. Moving forward, strengthening molecular databases, integrating advanced genomic tools, and building local research capacity are essential for comprehensive biodiversity assessment, effective monitoring, and informed conservation strategies in Bangladesh.Bioresearch Commu. 12(1): 2062-2069, 2026 (January)